Response Surface-Based Finite Element Model Updating of Steel Box-Girder Bridges with Concrete Composite Decks - Cheng-Qi Xiong; Zhi-Wen Zhu; Jin Jiang (Advances in Civil Engineering)
The orthotropic steel deck (OSD) using the steel-steel fiber reinforced concrete (SFRC) deck can be used in small and medium-span bridges for its advantages of construction convenience and lower construction cost. The seismic performance of THESE steel box girder bridges in strong earthquake zones needs to be evaluated, and a reasonable finite element model is the important basis for an accurate evaluation of these bridges. Finite element analysis (FEA) and field measurements of the dynamic characteristics of steel box girder bridges were carried out in this study, and the finite element model was updated based on the response surface method. The studies show that the bridge modal parameters can be reasonably identified based on the measurements of the bridge under ambient excitation without artificial excitation; the first six orders of mode shapes in the FEA results are consistent with the measured ones, but there is a difference between the natural frequencies; the model updating found that the elasticity modulus, density, and thickness of the SFRC have some influence on the first six orders of natural frequency of the bridge, but the SFRC thickness has the most significant influence on the bridge frequency, and the influence of epoxy asphalt pavement on bridge frequency is small. The study concluded that the SFRC layer of the bridge deck is no longer the traditional bridge deck pavement without considering the stiffness, but it integrates with the OSD as a steel-concrete composite structure. Therefore, the structure formed by the SFRC layer through the combination of shear studs and OSD shall be reasonably simulated in the finite element model so as to reasonably reflect the contribution of the SFRC layer in the composite structure of the bridge stiffness. The obtained updated finite element model gives results closer to the measured modalities, which provides a more reasonable bridge model for seismic analysis of bridges located in strong seismic zones and also demonstrates the effectiveness of the finite element analysis and the model updating method based on the response surface method in this study.